Space-body-ritual : performativity in the city - Tiwari, Reena, 1964- (Lexington Books, 2010)
Set against the contemporary thinking of the city as a spectacle, Space-Body-Ritual: Performativity in the City establishes everyday life in the city as a ground for authentic experience. Reena Tiwari emphasizes the city as a space of lived experience-an intricately layered space giving people a poetic experience, responding to their memories and desires. She also explores the conflict between two ideas: the idea of thee 'city as text' to be read and understood from a distance, and the 'city as body, ' where the body, after writing the text through its performance, achieves the capacity to read.